Korelasi NT-proBNP dengan Fraksi Ejeksi pada Pasien Gagal Jantung: Tinjauan Pustaka - Darma, I Wayan Dika Aditia; Sangging, Putu Ristyaning Ayu (CV. Jasa Sukses Abadi, 2026)
Heart failure is a complex clinical syndrome characterized by typical signs and symptoms resulting from structural or functional cardiac abnormalities that impair the ability of the ventricles to fill with or eject blood effectively. It remains a major global health problem with high morbidity and mortality rates. One of the most widely used biomarkers for assessing disease severity and prognosis in heart failure is N terminal pro brain natriuretic peptide or NT proBNP. Elevated NT proBNP levels occur in response to increased ventricular wall stress and volume overload and are closely related to the degree of left ventricular dysfunction, which is commonly assessed by left ventricular ejection fraction or LVEF. Numerous studies have demonstrated a significant negative correlation between NT proBNP levels and ejection fraction, particularly in patients with heart failure with reduced ejection fraction, where higher NT proBNP concentrations are observed as LVEF decreases. In contrast, in patients with heart failure with preserved ejection fraction, this relationship is not consistently linear. This variability is influenced by additional factors such as diastolic dysfunction, the presence of comorbid conditions, increased myocardial stiffness, and structural cardiac remodeling that may not be fully reflected by ejection fraction values alone. This literature review aims to analyze the relationship between NT proBNP levels and ejection fraction in patients with heart failure based on findings from national and international studies published over the past ten years. A clear understanding of this relationship is essential to define the diagnostic and prognostic value of NT proBNP and to support its use in therapeutic monitoring and risk stratification in patients with heart failure.